Dentures that keeps airway patent: a case report - Razak, Siti F. A.; Jamarun, Stacy A.; Sanudin, Siti H. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Foreign body aspiration is a life-threatening condition that requires immediate attention and intervention. Foreign body aspiration in adults usually occurs during dental procedure or motor vehicle trauma. Classical symptoms include choking, cough, haemoptysis, hoarseness or stridor. This case report presents an incident of a foreign body lodged at the subglottic region in an adult wearing dental prosthesis; the main complaint was hoarseness post motor vehicle accident. High index of suspicion coupled with correct investigation will facilitate the diagnosis of a foreign body in the airway thus immediate intervention can be taken to prevent morbidity and mortality.